Prevalence and Antibiotic Resistance of Escherichia coli Isolated from Raw Cow’s Milk - Roxana Ionela Drugea; Mădălina Iulia Siteavu; Elena Pitoiu; Cristina Delcaru; Ecaterina Monica Sârbu; Carmen Postolache; Stelian Bărăităreanu (Microorganisms)
Escherichia coli (E. coli) is one of the most common pathogens in both humans and livestock. This study aimed to investigate the prevalence of E. coli isolated from raw cow milk and evaluate its antimicrobial resistance rates. A total of 1696 milk samples were collected from Romanian dairy farms from 2018 to 2022. E. coli was isolated on various selective agar media, such as Cled agar and Columbia Agar with 5% Sheep Blood. The identification of E. coli was performed by MALDI-TOF MS. E. coli isolates were tested for their susceptibility against 18 commonly used antibiotics in a disk diffusion method. The overall prevalence of E. coli was 22.45% of all isolated pathogens. Antibiogram analysis revealed that 27.51% of E. coli isolates from milk were multidrug-resistant. Resistance was highest for penicillin–novobiocin (87.78%), followed by streptomycin (53.7%). Resistance to six drugs (amoxicillin, streptomycin, kanamycin–cephalexin, marbofloxacin, ampicillin) showed a significant increasing trend over time, while for two drugs (penicillin G-framycetin, doxycycline), a significant decrease was observed. Our results suggest that milk can be a reservoir of bacteria with the potential for infection in humans via the food chain. Furthermore, there is a need for surveillance and monitoring to control the increase in resistance to currently used antimicrobials in dairy farms because the occurrence of multidrug-resistant E. coli isolated from milk poses a health hazard to consumers.